The meaning of local wisdom in early childhood teacher’s experiences : a phenomenological study on culturally based learning - Siregar, Herlina; Pertiwi, Fitri; Maysara, Siska Resti (Universitas Islam Negeri Raden Intan Lampung, 2025)
Background: Banten possesses diverse forms of local wisdom such as Seba Baduy, Seren Taun, and coastal traditions; however, most early childhood education (ECE) teachers have not yet internalized the deeper meanings of these cultural practices, resulting in suboptimal integration into learning activities. Objective: This study aims to explore the lived experiences of ECE teachers in interpreting Banten’s local wisdom and identify factors influencing its implementation in early childhood learning. Methods: A qualitative phenomenological design was employed involving eight nonformal ECE teachers in Serang District selected through purposive sampling. Data were collected through indepth interviews, participant observation, and documentation. Subsequently analysed using processes of reduction, categorization, and interpretation of meaning. Results: Findings indicate that teachers recognize various cultural elements such as the Batu Kuwung folktale, the Maulid Nabi tradition, and the Jawara Banten song. However these elements are not applied systematically due to limited learning materials, insufficient cultural based training, and the predominance of non-local cultural content. Coastal values, including fishermen’s solidarity and marine environmental awareness, also remain underutilized despite their strong educational potential. Conclusion: Teachers’ understanding of Banten’s local wisdom remains largely conceptual, requiring strengthened pedagogical capacity and policy support to ensure that ECE learning becomes more contextual, meaningful, and rooted in local culture.